2004
DOI: 10.1016/j.molcel.2004.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Interference between Convergent Promoters Caused by Elongation over the Promoter

Abstract: Transcriptional interference with convergent transcription from face-to-face promoters is a potentially important form of gene regulation in all organisms. Using LacZ reporter studies, the mechanism of interference was determined for a pair of face-to-face prokaryotic promoters in which a strong promoter interferes 5.6-fold with a weak promoter, 62 bp away. The promoters were variously rearranged to test different models of interference. Terminating transcription from the strong promoter before it reached the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
200
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 166 publications
(212 citation statements)
references
References 31 publications
12
200
0
Order By: Relevance
“…It is not known whether both polymerases stall during collision and both 'fall off', whether one polymerase (randomly) is rescued from that stalled state by host factors and the other polymerase 'falls off ' [69] or whether a cooperative 'push' from following polymerases can influence the result [70]. We found that interference with transcription from the weak pL promoter of coliphage 186 increases the further its distance from the convergent strong pR promoter [20]. Our modelling [47] confirms the expectation that TI caused by collisions should increase as the distance between two convergent promoters is increased and as their activity is increased.…”
Section: Collisionsmentioning
confidence: 94%
See 4 more Smart Citations
“…It is not known whether both polymerases stall during collision and both 'fall off', whether one polymerase (randomly) is rescued from that stalled state by host factors and the other polymerase 'falls off ' [69] or whether a cooperative 'push' from following polymerases can influence the result [70]. We found that interference with transcription from the weak pL promoter of coliphage 186 increases the further its distance from the convergent strong pR promoter [20]. Our modelling [47] confirms the expectation that TI caused by collisions should increase as the distance between two convergent promoters is increased and as their activity is increased.…”
Section: Collisionsmentioning
confidence: 94%
“…Theoretically, an open complex bound at a promoter could act as a roadblock to the progress of an RNAP from another promoter. The in vitro data from Callen et al [20] indicate that the open complex at the coliphage 186 pL promoter does not hinder the progress of an elongating RNAP from pR. It is conceivable that some open complexes are so tightly bound that they could act as roadblocks rather than sitting ducks, but this possibility has not been confirmed.…”
Section: Roadblockmentioning
confidence: 99%
See 3 more Smart Citations